Moral Values in the Novel The Widow is My Mother by Kang Maman - Restiani Restiani; Erni Erni (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
The investigation of moral valuesw hich are present in the narrative and in which the widow is my mother is the study’s main challenge. The purpose of this study is to analyze the moral principles that underlie the short narrative. This study’s methodology is a qualitative descriptive approach. Researchers are involved in this investigation as observers and document collectors. My mother is the widow, and the manner of examination of moral principles in the book is the focus of this study. According to the researcher, the widow is my mother, and the research data for this study are quotations from the book. Techniques for taking notes and reading were used to obtain data for this study. The following three findings were drawn from the data analysis results. First, the relationship between people and themselves serves as a framework for analyzing the moral principles present in the book and the widow is my mother. The second is how people relate to each other. The third is the interaction between God and people.